Characteristics and Histopathological Features of Breast Tumor Patients at RSUD dr. Chasbullah Abdulmadjid Bekasi City 2019-2023 - Angeline, Reni; Husseynia Muharrani; Shintia Christina; Freciyana Boedijono (Universitas Kristen Krida Wacana, 2024)
Globocan data for 2020 in the world, breast cancer cases are in first place with 2,261,419 cases, the death rate is in fifth place with 684,994 people. In Indonesia, in 2020 breast cancer ranks first. In the 2020 Bekasi City health profile data, there were 92 cases (4.8%) of breast lumps/tumors, compared to 2019 was 6.37%, but when compared to 2018, there was an increase in cases of 4.18%. The aim of this study was to find out information on the characteristics and histopathological features of breast tumor patients at RSUD dr. Chasbullah Abdulmadjid Bekasi City in 2019-2023. This research is a descriptive study with a cross-sectional method, using secondary data from anatomical pathology archives. In the study, a total of 488 cases of benign and malignant breast tumors were found, consisting of: 176 cases in 2019, 97 cases in 2020, 77 cases in 2021, 69 cases in 2022, and 69 cases in 2023. Description of tumor incidence Most benign breasts at the age of 20-29 years, location of upper lateral quadrant tumors, clinical diagnosis of benign breast tumors and histopathological type of mammary fibroadenoma. Meanwhile, the description of the incidence of malignant breast tumors is highest at age > 50 years, location of the upper lateral quadrant tumor, clinical diagnosis and histopathological type of invasive ductal carcinoma.